Trust and knowledge contribution to agricultural cluster performance (2020)
Purpose This paper aimed to analyze the contribution of the interorganizational relationship (IOR) factors trust and knowledge resources to the relational and transactional performance of a Brazilian agricultural cluster formed by small farmers. Design/methodology/approach A survey was conducted using a questionnaire divided into groups of variables, each group seeking to identify one of the three constructs: trust, knowledge resources and relational and transactional performance. A theoretical framework was elaborated and later compared with survey results, which were analyzed using exploratory factor analysis (EFA) and partial least squares–structural equation modeling (PLS-SEM). Findings Correlations between trust and relational and transactional cluster performance varied according to actors involved, being significant between some actors and not significant between others. Knowledge resources, on the other hand, proved to be significantly relevant for cluster performance, considering both relational and transactional measures. Research limitations/implications It was made in a Brazilian single cluster and its conclusions cannot be generalized. Practical implications Farmers cannot innovate with the efficiency and effectiveness that the process demands. They need complementary capacity that apparently is not in the agricultural cluster. Research and development involve knowledge and techniques that empirical knowledge alone may not provide. And much of the formal knowledge is embedded in universities and research institutes. If there were investments by public entities in research and development to improve the culture and its by-products, this could contribute to improving the income of farmers. Social implications This study provided a photograph of the current scenario of a Brazilian agricultural cluster. Changes in trust and knowledge resources could affect cluster relational and transactional performance. Special attention is deserved to the important role of scientific research on agricultural clusters to strengthen the capacity of critical analysis by the researcher who, with the results in hand, makes them public, hoping that the shared information can contribute with the research of other scholars and improve the quality of life of farmers involved. Originality/value This study offers empirical evidence that trust and knowledge resources can contribute to a Brazilian agricultural cluster performance, which can be analyzed considering both relational and transactional measures. These findings brought new fact to Singh and Shrivastava’s (2013) research.